Arbuscular Mycorrhizal Fungi Regulate Polyamine Homeostasis in Roots of Trifoliate Orange for Improved Adaptation to Soil Moisture Deficit Stress - Zou, Ying-Ning; Zhang, Fei; Srivastava, Anoop K.; Wu, Qiang-Sheng; Kuča, Kamil (Frontiers in Plant Science, 2021)
Soil arbuscular mycorrhizal fungi (AMF) enhance the tolerance of plants against soil moisture deficit stress (SMDS), but the underlying mechanisms are still not fully understood. Polyamines (PAs) as low-molecular-weight, aliphatic polycations have strong roles in abiotic stress tolerance of plants. We aimed to investigate the effect of AMF (Funneliformis mosseae) inoculation on PAs, PA precursors, activities of PA synthases and degrading enzymes, and concentration of reactive oxygen species in the roots of trifoliate orange (Poncirus trifoliata) subjected to 15 days of SMDS. Leaf water potential and total chlorophyll levels were comparatively higher in AMF-inoculated than in non-AMF-treated plants exposed to SMDS. Mycorrhizal plants recorded a significantly higher concentration of precursors of PA synthesis such as L-ornithine, agmatine, and S-adenosyl methionine, besides higher putrescine and cadaverine and lower spermidine during the 15 days of SMDS. AMF-colonization raised the PA synthase (arginine decarboxylase, ornithine decarboxylase, spermidine synthase, and spermine synthase) activities, and PA degrading enzymes (copper-containing diamine oxidase and FAD-containing polyamine oxidase) in response to SMDS. However, mycorrhizal plants showed a relatively lower degree of membrane lipid peroxidation, superoxide anion free radical, and hydrogen peroxide than non-mycorrhizal plants, whereas the difference between them increased linearly upto 15 days of SMDS. Our study concluded that AMF regulated PA homeostasis in roots of trifoliate orange to tolerate SMDS.